Effects of laser shock peening on the surface integrity of 18 % Ni maraging steel - Petan, Luca (Strojniški vestnik, 2016)
Maraging steels represent a special group of steels where ultrahigh strength is achieved with precipitation hardening. Because of their superior mechanical properties, maraging steels are used for the manufacturing of parts in the aerospace and tooling industry. Usually these mechanical components operate in demanding environments and conditions where they are subject to mechanical fatigue, thermo- mechanical fatigue, corrosion, and wear. The scope of the research presented in this paper is to analyze the effects of laser shock peening (LSP) on surface integrity characteristics of X2NiCoMo18-9-5 maraging steel. In this study, maraging steel specimens, in both quenched and aged condition, were treated with LSP by varying the pulse density. The effects of laser treatment on surface integrity were analyzed with roughness, residual stress, and microhardness measurements. According to the measurement results, LSP generated high compressive residual stresses in the steel surface layer with relatively low surface roughness, which indicates possible fatigue resistance improvements in 18 % Ni maraging steel.
Keywords: hrapavost površine; lasersko udarno utrjevanje; mikrotrdota; tlačne zaostale napetosti